IMPLEMENTASI KONSEP DAN TEORI PEMBELAJARAN PENDIDIKAN ISLAM DI MAN PERSIAPAN IV KOTA MEDAN - Anri Naldi; Cahaya Cahaya (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to analyze the implementation of Islamic education learning concepts and theories at MAN Persiapan IV in Medan. This qualitative research, using a phenomenological approach, employed data collection techniques such as observation, interviews, and document analysis. Primary data was obtained through observations and interviews, while secondary data came from document studies. Data analysis followed the Miles and Huberman approach. The findings reveal that the learning concepts and theories in Islamic education cannot be separated, as they align with the current curriculum, providing a deeper understanding of the meaning of learning. However, a challenge identified is the need to integrate these concepts and theories with the development of media and technology. The study concludes that the correlation between learning concepts and theories in Islamic education must be adapted to technological advancements to achieve the optimal goals of Islamic education.